From where we intervene when we intervene? The case of the "Tomato Platense Project" - Garat, Juan José; Otero, Jeremías (Centro de Historia Argentina y Americana, 2012)
This work proposes a critical thought on an intervention experience [the "tomato platense" project] in which the authors of this article have participated since its beginning. Such thought implies to put in evidence and discussion, the "what" and the "how" of the intervention for rural development. For this, we work the concepts of: models of development and intervention, technology, hegemony and family farming; and we propose at the same time, a case study methodological strategy. Subsequently, we carry out a description of the intervention process, identifying stages and highlighting aspects that we consider significant. In that regard we envision a process of legitimization of an alternative proposal, which means in a sense a break-up of the technology spiral dominant present in horticultural belt of La Plata. The initial formulation of the proposal arises from a diagnosis made in Cabinet, in the Faculty of Agricultural and Forest Sciences of the UNLP, which has a later participatory becoming, involving partial and periodic reformulation of the initial proposal